Optimisation of raw tooke flour, vital gluten and water absorption in tooke/wheat composite bread: Effect of raw tooke flour and vital gluten on wheat flour physicochemical and dough rheological properties (Part I) - Muranga, Florence I.; Mutambuka, Martin; Nabugoomu, Fabian; Lindhauer, M. G. (African Journal of Food Science, 2010)
Raw Tooke Flour (RTF) is a generic, shelf stable flour from matooke (a cooking banana variety) targeting the baking industry. However, its lack of gluten has hampered development of RTF/wheat composite bread. It is thus necessary to optimize levels of substitution of RTF into wheat flour with vital gluten as a processing aid for improving rheological and baking properties. The specific objective of this study was to determine effect of RTF (0 - 33%) and vital gluten (0 - 3%) on wheat flour pasting and dough rheological properties. The Rapid Visco Analyser was used to measure flour pasting properties while the Farinograph and Extensograph measured dough rheology. Response Surface Methodology (RSM) procedures were used to relate variables to dough rheological properties. RTF significantly increased the pasting profile of wheat flour (by increasing peak, minimum and final viscosities). It weakened the dough (by increasing degree of softening; reducing dough stability and extensibility) while vital gluten strengthened it. Water absorption increased with both variables while dough development time (DDT) was reduced by RTF. Though vital gluten improved dough properties, it did not effectively counteract the negative effects of RTF at the levels applied in the study.
Keywords: Composite bread; pasting properties; farinograph; extensograph; RSM